1996
DOI: 10.1046/j.1365-2303.1996.37382373.x
|View full text |Cite
|
Sign up to set email alerts
|

Glandular lesions of the cervix—cytological and histological correlation

Abstract: In this retrospective review we assessed the frequency with which atypical glandular cells in cervical smears predict cervical glandular lesions. Asymptomatic patients (n=34) with one or more smears showing atypical glandular cells aand subsequent histopathological assessment were studied. Independent cytological and histological review was undertaken. Cytological review confirmed atypical glandular cells in 29 cases, 17 of which had coexisting squamous dyskaryosis. Histological review of these 29 cases reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
3
16
0
1
Order By: Relevance
“…In a study of Raab SS and co-workers [23] an interobserver variability of Papanicolaou smear diagnoses of atypical glandular cells of undetermined significance with a sensitivity of only 63% and a specificity of 58% is reported. Our tissue-proven follow-up findings are summarized in Table 4, and regroup the spectrum of potential pitfalls, that had also been reported by other groups [30,33-38]. So 31 of our AGC-cases were associated with tissue-proven endocervical squamous lesions, 28 corresponding to squamous intraepithelial lesions and 3 to invasive squamous carcinomas and benign lesions such as irritated endocervical and endometrial polyps or glandular hyperplasia.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In a study of Raab SS and co-workers [23] an interobserver variability of Papanicolaou smear diagnoses of atypical glandular cells of undetermined significance with a sensitivity of only 63% and a specificity of 58% is reported. Our tissue-proven follow-up findings are summarized in Table 4, and regroup the spectrum of potential pitfalls, that had also been reported by other groups [30,33-38]. So 31 of our AGC-cases were associated with tissue-proven endocervical squamous lesions, 28 corresponding to squamous intraepithelial lesions and 3 to invasive squamous carcinomas and benign lesions such as irritated endocervical and endometrial polyps or glandular hyperplasia.…”
Section: Discussionsupporting
confidence: 63%
“…All of there 15 endometrial AC were symptomatic. Jackson et al [30] reported a series of 34 asymptomatic cases giving a final outcome of cervical glandular neoplasia in 45% including just one case of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The stroma between glands is minimal to absent, giving a cribriform pattern, and hence the worry that the lesion is malignant. Vacuolated and occasionally clear cells may be present, and hence the lesion may be confused with clear cell invasive adenocarcinoma (31) .…”
Section: Pathology Of Cervical Glandular Neoplasiamentioning
confidence: 99%
“…Cytology plays an important role in the diagnosis and follow-up of endocervical lesions since these cellular changes do not frequently have clinical diagnostic symptoms or characteristic colposcopic features. 3,8,15,28 Though better detection has led to an increase in the identification of AC and its precursors, endocervical lesions may still be overlooked: their cytologic criteria are not well known or completely reproducible. Moreover, benign cervical changes, such as Arias-Stella reaction, microglandular hyperplasia, tubal or endometrial metaplasia, cervical endometriosis and mesonephric remnants, may be potential pitfalls in the cytologic diagnosis of adenocarcinoma in situ (AIS) or even AC.…”
Section: Objective: To Determine Whether Evaluating Morphologic Featumentioning
confidence: 99%